First-person accounts of the processes and planning involved in a suicide attempt on the railway. Issue 1 (20th January 2021) - Marsh, Ian; Marzano, Lisa; Mosse, David; Mackenzie, Jay-Marie
Abstract : Background: The processes and planning involved in choosing and attempting to die by a particular method of suicide are not well understood. Accounts from those who have thought about or attempted suicide using a specific method might allow us to better understand the ways in which people come to think about, plan and enact a suicide attempt. Aims: To understand from first-person accounts the processes and planning involved in a suicide attempt on the railway. Method: Thematic analysis was conducted of qualitative interviews ( N = 34) undertaken with individuals who had contemplated or attempted suicide by train. Results: Participants explained how they decided upon a particular method, time and place for a suicide attempt. Plans were described as being contingent on a number of elements (including the likelihood of being seen or interrupted), rather than being fixed in advance. Participants mentally rehearsed and evaluated a particular method, which would sometimes involve imagining in detail what would happen before, during and after an attempt. The extent to which this involved others (train drivers, partners, friends) was striking. Conclusions: By giving people free reign to describe in their own words the processes they went through in planning and undertaking a suicide attempt, and by not interpreting such accounts through a lens of deficit and pathology, we can arrive at important insights into how people come to think and feel about, plan and enact a suicide attempt. The findings have implications in terms of understanding suicide risk and prevention more broadly.